TRANSLATION PROBLEMS OF IDIOMS DENOTING “HUMAN APPEARANCES” IN ENGLISH AND UZBEK - Mukhtorova Dilfuza (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Idioms are culturally-bound expressions that often resist literal translation. When idioms denote aspects of human appearance, they become even more challenging due to cultural differences, metaphorical meaning, and contextual usage. This article explores the major translation issues of idioms related to human appearances, using English and Uzbek as a case study, and discusses strategies to address these challenges.